2021
DOI: 10.1371/journal.pone.0253216
|View full text |Cite|
|
Sign up to set email alerts
|

Queuine, a bacterial-derived hypermodified nucleobase, shows protection in in vitro models of neurodegeneration

Abstract: Growing evidence suggests that human gut bacteria, which comprise the microbiome, are linked to several neurodegenerative disorders. An imbalance in the bacterial population in the gut of Parkinson’s disease (PD) and Alzheimer’s disease (AD) patients has been detected in several studies. This dysbiosis very likely decreases or increases microbiome-derived molecules that are protective or detrimental, respectively, to the human body and those changes are communicated to the brain through the so-called ‘gut-brai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 64 publications
2
14
0
Order By: Relevance
“…Eukaryotes are not capable of Q synthesis and rely on salvage of the queuine base as a Q precursor either by nutrition or by the intestinal bacterial flora ( Farkas, 1980 ; Katze et al, 1982 ; Ott et al, 1982 ). Queuine has been associated with neuroprotection ( Richard et al, 2021 ) whereas absence of queuine is associated with better cancer cells growth and survival by promoting Warburg metabolism ( Hayes et al, 2020 ). The tRNA-guanine transglycosylase (TGT) is the main enzyme responsible for the formation of Q in the anticodon loop position 34 of tRNA Asp , tRNA His , tRNA Asn and tRNA Tyr .…”
Section: Current Knowledge Of the Epigenetic Mechanisms Characterized...mentioning
confidence: 99%
“…Eukaryotes are not capable of Q synthesis and rely on salvage of the queuine base as a Q precursor either by nutrition or by the intestinal bacterial flora ( Farkas, 1980 ; Katze et al, 1982 ; Ott et al, 1982 ). Queuine has been associated with neuroprotection ( Richard et al, 2021 ) whereas absence of queuine is associated with better cancer cells growth and survival by promoting Warburg metabolism ( Hayes et al, 2020 ). The tRNA-guanine transglycosylase (TGT) is the main enzyme responsible for the formation of Q in the anticodon loop position 34 of tRNA Asp , tRNA His , tRNA Asn and tRNA Tyr .…”
Section: Current Knowledge Of the Epigenetic Mechanisms Characterized...mentioning
confidence: 99%
“…In mammals, gut availability of queuine affects virulence of resident gut microbes ( 10 ) and modulates cancer growth ( 11 , 12 ). Q-modification levels in tRNA are especially high in human brain tissues ( 13 ) and queuine also plays a role in resistance to cancer metabolism ( 11 ) and neuronal damage ( 14 ). Since queuine must be scavenged from the gut and Q-tRNA modification is directly involved in protein biosynthesis, queuine and Q-tRNA modification present a clear connection between the gut microbiome and host proteostasis.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of numerous described Q-dependent implications in various diseases, starting from cancer ( 29–32 ) to neurological and neuropsychiatric disorders, such as multiple sclerosis, schizophrenia and Parkinson ( 79 , 80 , 33 , 34 ), a defined mechanism explaining the role of Q in these pathologies is still missing ( 28 ). Recently, we discovered a direct connection between Q, accuracy and the speed of codon-biased translation ( 27 , 28 ), which promotes protein folding and prevents the accumulation of misfolded proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies in eukaryotes likewise reported an impact on the decoding process, enabling decoding of synonymous codons by wobble base pairing ( 22 , 25 , 26 ), and affecting translation speed and accuracy ( 27 , 28 ). Queuosine's multifaceted involvement in the cellular machinery was reported to be associated with cancer ( 29–32 ), neuronal disorders ( 33–35 ) as well as bacterial and parasitic infection ( 36 , 37 ). Consequently, the perception of therapeutic potential associated with its biogenesis has consistently increased, in keeping with a general trend in epitranscriptomics…”
Section: Introductionmentioning
confidence: 99%